Leonid Evseevich Cherkassky in China - Z. Liu (Научный диалог, 2018)
The article deals with the issue of the activity of the outstanding Russian sinologist, translator of Chinese literature Leonid Evseevich Cherkassky. The purpose of the study is to describe the activities of Cherkassky, in particular, his works related to the translation of Chinese poetry. Attention is paid to the research of scientific and literary creativity of the Russian sinologist. The novelty of the work is seen in the fact that at the moment there is no detailed study of the reception of China by Cherkassky as an outstanding expert of Chinese culture. The relevance of the work is determined by the need to study the activities of a highly professional master sinologist to understand the uniqueness of the Russian-Chinese literary relations, which meets the trends of modern comparative literature studies, in which the issues related to translated literature are among the most important problems. It is noted that, based on the work of leading Chinese specialists in Russian philology, mainly, translator Song Shaoхiang, one can make a conclusion, firstly, about the significance of the activities of Cherkassky for the development of Chinese-Russian literary relations, and secondly, about special merit of Professor Song Shaoхiang in the revealing the posthumous work of Leonid Evseevich “Xu Zhimo: Flights in Dreams and Reality,” which is an in-depth study of the life and works of the Chinese poet, novelist and scholar Xu Zhimo.